If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/2x+1/2x=1+x
We move all terms to the left:
1/2x+1/2x-(1+x)=0
Domain of the equation: 2x!=0We add all the numbers together, and all the variables
x!=0/2
x!=0
x∈R
1/2x+1/2x-(x+1)=0
We get rid of parentheses
1/2x+1/2x-x-1=0
We multiply all the terms by the denominator
-x*2x-1*2x+1+1=0
We add all the numbers together, and all the variables
-x*2x-1*2x+2=0
Wy multiply elements
-2x^2-2x+2=0
a = -2; b = -2; c = +2;
Δ = b2-4ac
Δ = -22-4·(-2)·2
Δ = 20
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{20}=\sqrt{4*5}=\sqrt{4}*\sqrt{5}=2\sqrt{5}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2\sqrt{5}}{2*-2}=\frac{2-2\sqrt{5}}{-4} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2\sqrt{5}}{2*-2}=\frac{2+2\sqrt{5}}{-4} $
| -7(x+7)=15 | | -9(6n-5)-3=-336 | | 13+19=-4(2x-8) | | 2x-17+8+2=x+20 | | -7x+10=-x+70 | | 2(5x-3)=3(3x-2)+x | | -(x)=9 | | U=-5u+6u | | 7x/4+48=13x/4 | | s11-s=24 | | x-5=-6x+58 | | 63=-1x | | -(-x)=-9 | | 7x/4+48=13x/44 | | -3=15-2/3x | | 2x+52=-x/6 | | 2=-8/b | | 18(x+12)=7 | | 7x+2=-5+5x+11 | | -20-4x=-6-16 | | 100x-10x=77.7-7.7 | | -10+9p=p+8p-10 | | 6+x+12=20 | | |4a+5|=|3a-2| | | x+1+2x+5=4x+2 | | f+82=84 | | -(-x)=9 | | s-9=(6+-8 | | 6/8x+4=34 | | 14.68=2y | | 8/3x-2=4+2/3x | | 1/2(5-2h)=h |